2016
DOI: 10.1007/s12199-016-0542-2
|View full text |Cite
|
Sign up to set email alerts
|

Rural–urban differences in the prevalence of cognitive impairment in independent community-dwelling elderly residents of Ojiya city, Niigata Prefecture, Japan

Abstract: The prevalence of cognitive impairment was higher in the rural area relative to urban areas in Ojiya city. This regional difference suggests the existence of potentially modifiable factors other than lifestyle in relation to cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 29 publications
(44 reference statements)
5
38
1
Order By: Relevance
“…However, our results were contrary to those of a Japanese study that included urban and rural populations of people over 65 years of age, which showed that the prevalence of male cognitive impairment was 6.6% and that of female cognitive impairment was 3.4% [13]. The cause of higher prevalence of nonvascular cognitive impairment in this study may be explained by the limited criteria of exclusion.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, our results were contrary to those of a Japanese study that included urban and rural populations of people over 65 years of age, which showed that the prevalence of male cognitive impairment was 6.6% and that of female cognitive impairment was 3.4% [13]. The cause of higher prevalence of nonvascular cognitive impairment in this study may be explained by the limited criteria of exclusion.…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of dementia and cognitive impairment has been inconsistent across regions and people, but almost all previous studies showed that the prevalence of cognitive impairment was higher in women than in men [13,14,16,19,27]. A study from a population in northern Portugal that included participants aged 55-79 years old showed that the prevalence of cognitive impairment was higher in women than in men in both urban and rural areas, as follows: 13.7 versus 9.4% and 18.2 versus 14.8% respectively [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several epidemiological studies have indicated a cognitive advantage of living in urban rather than rural areas (5,(15)(16)(17). However, the moderating role of disabilities has been investigated in very few studies.…”
Section: Introductionmentioning
confidence: 99%